Responding to changing needs : developments and trends in social security throughout the world, 1990-1992 : report 1 (General Secretariat of the ISSA GenevaCH, 1993)
Provides an analysis of the trends and development that have taken place during the period under review. Focuses on the responses by governments and social security institutions to the increasing demands being placed on the different branches of security. Raises the question of whether the existing traditional structures will be able to cope with these additional pressures, or whether a new more radical approach will be required.
DC